Why the Isles, why the continent? Reasons for choosing particular countries of emigration among post-EU accession migrants from Poland - Dominika Pszczółkowska (University of Warsaw, Centre of Migration Research (CMR), 2015)
After Poland joined the EU in 2004, Polish migration routes changed dramatically. The United Kingdom replaced Germany as the preferred destination. Some completely new countries - such as Ireland - appeared on the map of Polish migrations. Much research has been devoted to this great movement, but there is still no complete answer to the question why particular migrants choose particular destinations, for example why young and educated Poles head for Ireland, but very infrequently for the Netherlands. The purpose of this article is to review existing knowledge on post-accession migration from the perspective of country choice. Initially, legal reasons were emphasized in the literature. Some scholars assumed that the whole very large difference between predicted and actual migrant inflows by country was due to the so called diversion effect, or the redirecting of Central and Eastern European migrants from Germany to the UK and Ireland due to the earlier opening of these labour markets. An even larger body of research underlines economic reasons: the availability of jobs and high wages that attracted migrants. More recently several studies painted a more complex picture, in which many Poles in the UK and Ireland migrated for cultural reasons, such as education, language acquisition or a different lifestyle. Researchers do not agree on the influence of social factors, particularly migrant networks, on migrants' choice of destination.
Keywords: 330; EU; Poland; post-accession migration; destination choice; diversion effect